2016
DOI: 10.1042/bst20160023
|View full text |Cite
|
Sign up to set email alerts
|

Purification of bacterial membrane sensor kinases and biophysical methods for determination of their ligand and inhibitor interactions

Abstract: This article reviews current methods for the reliable heterologous overexpression in Escherichia coli and purification of milligram quantities of bacterial membrane sensor kinase (MSK) proteins belonging to the two-component signal transduction family of integral membrane proteins. Many of these methods were developed at Leeds alongside Professor Steve Baldwin to whom this review is dedicated. It also reviews two biophysical methods that we have adapted successfully for studies of purified MSKs and other membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…However, other studies contested this model, reporting the lack of a VanS A ‐vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol‐solubilized VanS A are not altered in the presence of vancomycin . A possible explanation of the contradictory results of these latter studies can be due to the VanS A solubilization using detergents, which are known to affect the function of sensor kinase membrane proteins . Furthermore, the in vitro experimental setup in these studies also lacks the target of vancomycin – the d ‐Ala‐ d ‐Ala group of lipid II, and thus do not necessarily reflect the natural environment of VanS wherein the protein could form a proposed VanS A ‐lipid II‐vancomycin complex …”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 98%
See 1 more Smart Citation
“…However, other studies contested this model, reporting the lack of a VanS A ‐vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol‐solubilized VanS A are not altered in the presence of vancomycin . A possible explanation of the contradictory results of these latter studies can be due to the VanS A solubilization using detergents, which are known to affect the function of sensor kinase membrane proteins . Furthermore, the in vitro experimental setup in these studies also lacks the target of vancomycin – the d ‐Ala‐ d ‐Ala group of lipid II, and thus do not necessarily reflect the natural environment of VanS wherein the protein could form a proposed VanS A ‐lipid II‐vancomycin complex …”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 98%
“…50 A possible explanation of the contradictory results of these latter studies can be due to the VanS A solubilization using detergents, which are known to affect the function of sensor kinase membrane proteins. 50,53 Furthermore, the in vitro experimental setup in these studies also lacks the target of vancomycinthe D-Ala-D-Ala group of lipid II, and thus do not necessarily reflect the natural environment of VanS wherein the protein could form a proposed VanS Alipid II-vancomycin complex. 54 In an attempt to minimize the effect of detergent, the S. coelicolor VanS (VanSSc) was recombinantly expressed and purified from S. coelicolor and E. coli membranes and shown to bind a photo-labeled vancomycin derivative.…”
Section: Vans Sensor Kinasementioning
confidence: 99%
“…As such, structural characterisation of VanS is highly challenging. While recent studies have demonstrated production of highly pure and active samples of A-type VanS 38,53,54 which have been characterised using techniques including circular dichroism and analytical ultracentrifugation, characterisation via high-resolution methods such as X-ray crystallography and NMR spectroscopy has met with very little success. Thus far, structural understanding of VanS has been gleaned from comparison to other sensor histidine kinases of known structure.…”
Section: Discussionmentioning
confidence: 99%
“…The fsrB gene (EF1821) of E. faecalis V583 was cloned into expression plasmid pTTQ18His as described previously . Briefly, primers FsrB‐F: 5′‐CCGGAATTCCCTAATCGATTGGATTCTAAAAAATATTATGG‐3′ and FsrB‐R: 5′‐AAAACTGCAGCTGCAAAAACACTTCCTTCAATTAAATTTTTTG‐3′ were used to amplify the fsrB gene from E. faecalis V583 genomic DNA using polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%
“…CD measurements were made using the nitrogen‐flushed instrument on the B23 Synchrotron Radiation CD Beamline at the Diamond Light Source, Oxfordshire, UK, as described previously . Purified FsrB was prepared in HGSD buffer.…”
Section: Methodsmentioning
confidence: 99%